Indonesian and United States of American Economic Partnership Agreement Effect - Tajerin, Tajerin (Economic Journal of Emerging Markets, 2011)
The paper analyzes fisheries trade effects from the implementation of Indonesian and the United States of American Economic Partnership Agreement (IUSEPA). The analysis is performed on the integrated world trade databases owned by World Trade Organization, United Nations Conference on Trade and Development, and United Nations Statistics Division, using Wits software package developed by the World Bank. The result indicates that in the future, Indonesian government as a party that will conduct bilateral economic partnership agreement with the United states, needs to propose or negotiate fishery import tariffs that imposed by the United States ranges from 0 to 7 percent. Keywords: Bilateral economic agreement, fisheries, trade effect